Oral health status of patients after replacement of removable partial dentures after three years - naje, sahar (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): To assess the effect of removable partial dentures on the abutment teeth in comparison with that of theremaining dentition, and to investigate the effect of regular check up on periodontal health for patients using thistype of prosthesis.Methodology: One hundred patients wearing removable partial dentures for at least three years included in thestudy. Teeth used as direct or in direct retainers for the removable partial denture were considered as the studygroup, while the remaining dentition in the same jaw was considered as the control group. The following periodontalparameters were registered for each tooth, plaque and gingival indices, clinical attachment level and tooth mobility.Patients were divided into two groups as regular and irregular attendants.Results: Among the 100 patient, 30 were regular attendants. A significant difference in clinical attachment level andplaque accumulation was detected between study and control group of teeth. In addition there was a statisticallysignificant difference in all periodontal parameters between regular and irregular attendantsResults: Among the 100 patient, 30 were regular attendants. A significant difference in clinical attachment level andplaque accumulation was detected between study and control group of teeth. In addition there was a statisticallysignificant difference in all periodontal parameters between regular and irregular attendants.Recommendations: The Patient palaces for removable partial denture must maintain visits so we can check theremovable partial denture and supporting teeth for any problem. Also, call for an appointment as soon as you developany problem with your denture.